SARS-CoV-2 seroprevalence in Aden, Yemen: a population-based study. (February 2022) - Bin-Ghouth, Abdulla Salem; Al-Shoteri, Sheikh; Mahmoud, Nuha; Musani, Altaf; Baoom, Nasser Mohsen; Al-Waleedi, Ali Ahmed; Buliva, Evans; Aly, Eman AbdelKreem; Naiene, Jeremias Domingos; Crestani, Rosa; Senga, Mikiko; Barakat, Amal; et al.
Highlights: The prevalence of severe acute respiratory syndrome coronavirus-2 antibodies in a population from Aden, Yemen was high (27.4%). The prevalence of coronavirus disease 2019 (COVID-19) was higher among females than males. Household contacts are the social groups with greatest exposure to infection. The prevalence of asymptomatic COVID-19 was low (7.8%) among the study participants. SUMMARY: Background: In Yemen, initial surveillance of coronavirus disease 2019 (COVID-19) focused primarily on patients with symptoms or severe disease. The full spectrum of the disease remains unclear. To the best of the authors' knowledge, this is the first seroprevalence study performed in Yemen. Methods: This cross-sectional investigation included 2001 participants from all age groups from four districts in Aden, southern Yemen. A multi-stage sampling method was used. Data were collected using a well-structured questionnaire, and blood samples were taken. Healgen COVID-19 IgG/IgM Rapid Diagnostic Test (RDT) Cassettes were used in all participants. All positive RDTs and 14% of negative RDTs underwent enzyme-linked immunosorbent assay (ELISA) testing (WANTAI SARS-CoV-2 Ab ELISA Kit) for confirmation. Results: In total, 549 of 2001 participants were RDT positive and confirmed by ELISA, giving a prevalence of COVID-19 of 27.4%. The prevalence of immunoglobulin G was 25%. The prevalence of asymptomatic COVID-19 in the entire study group was 7.9%. The highest prevalence was observed in Al-Mansurah district (33.4%). Regarding sociodemographic factors, the prevalence of COVID-19 was significantly higher among females, housewives and subjects with a history of contact with a COVID-19 patient: 32%, 31% and 39%, respectively. Conclusion: This study found high prevalence of COVID-19 in the study population. Household transmission was common.